Effects of non-ionizing radiation of cell tower (CT) and high voltage transmission line (HVTL) on plants, animals and humans - Asad, Mahamud; Naireet, Uddipto Islam; Gupta, Ayush Datta (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2024.